Meaning and Content of Brand Consciousness for Middle Income Families - Agarwal, Pankaj (International Journal of Psychosocial Rehabilitation, 2019)
According to a research by PricewaterhouseCoopers (PwC), he is displaying a stronger affinity for high-end fashion with his growing penchant for premium names and his readiness to experiment with mass-market products. The PwC study "From Sao Paulo to Shanghai-New consumer dynamics: the impact on modern retailing" found that "consumers equate brands with an intangible value for which they are willing to pay premium prices." PwC reports that urban India’s upper and middle classes have increased their discretionary spending by 16%, with much of the increase going toward personal care and clothing purchases due to the rising importance placed on "looking good." The survey notes that the rising cost of such activities can be attributed to the rise of "new malls offering multiplexes, restaurants and bars, video games centers in both large and smaller cities," among other things. Disposable earnings in India are projected to rise by 8.5% year until 2015, thanks to the country’s rapid economic expansion.